2011
DOI: 10.1186/1471-244x-11-1
|View full text |Cite
|
Sign up to set email alerts
|

ALGOS: the development of a randomized controlled trial testing a case management algorithm designed to reduce suicide risk among suicide attempters

Abstract: BackgroundSuicide attempts (SA) constitute a serious clinical problem. People who attempt suicide are at high risk of further repetition. However, no interventions have been shown to be effective in reducing repetition in this group of patients.Methods/DesignMulticentre randomized controlled trial.We examine the effectiveness of «ALGOS algorithm»: an intervention based in a decisional tree of contact type which aims at reducing the incidence of repeated suicide attempt during 6 months. This algorithm of case m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
135
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 15 publications
7
135
5
2
Order By: Relevance
“…Furthermore, regular telephone contact allow an earlier detection of increased risk of suicide repetition and to take appropriate measures to prevent suicide completion, rather than a single telephone contact. In this line, the Vaiva et al project suggests the ALGOS algorithm that includes the strategy of sending short letters to certain patients in order to improve the "connectedness" (191). However, with a single telephone call it seems unlikely that the rate of further suicide attempts can be reduced by 12% in 13 months, as obtained in their previous study (165).…”
Section: Chapter 5 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, regular telephone contact allow an earlier detection of increased risk of suicide repetition and to take appropriate measures to prevent suicide completion, rather than a single telephone contact. In this line, the Vaiva et al project suggests the ALGOS algorithm that includes the strategy of sending short letters to certain patients in order to improve the "connectedness" (191). However, with a single telephone call it seems unlikely that the rate of further suicide attempts can be reduced by 12% in 13 months, as obtained in their previous study (165).…”
Section: Chapter 5 Discussionmentioning
confidence: 99%
“…This is of particular interest given that over 40% of patients who completed suicides received psychiatric attention for self-harm in the emergency departments during the previous year (191).…”
Section: Chapter 5 Discussionmentioning
confidence: 99%
“…Members of our group have experience in multicenter randomized controlled trials using interventions such as phone calls to reduce the incidence of repeated suicide attempts (Vaiva et al, 2006;Vaiva et al, 2011).…”
mentioning
confidence: 99%
“…In many ways this was a composite of interventions to date, 146 and similar to a planned intervention in France. 158 With respect to the main aim of our study, we found that carrying out a pilot randomised trial of our intervention was challenging but feasible.…”
Section: Resultsmentioning
confidence: 99%